PROSPEK EKONOMI INDONESIA: PERSPEKTIF MAKROEKONOMI : Prospek Ekonomi Indonesia: Perspektif Makroekonomi - Maryanti, Sri; Widayat, Prama; Lubis, Nurhayani (Universitas Lancang Kuning, 2023)
This study is a literary study that aims to analyze Indonesia's economic prospects from a macroeconomic perspective. This is very important considering that macroeconomic variables are very much used as indicators in economic development and growth. Such as inflation, the rate of population growth and so on. From this literature study, it was obtained that the Indonesian Economic Prospects for the future cannot be categorized as having a better prospect, this can be seen in the high level of displacement until 2022, even world economic observers think it is difficult for Indonesia to be able to suppress the growth rate of unemployment considering that during the Covid-19 pandemic alone there have been many layoffs. In addition, the inflation rate tends to increase due to the impact of the increase in consumer prices in Indonesia coupled with the Russian invasion of Ukraiana which also has an indirect impact on Indonesia considering that Russia controls world gas and many European Union countries are very dependent on Russia.